Interactions with children with autism spectrum disorders in a speech therapy setting / Zeena Mahmood Ameen - Zeena, Mahmood Ameen (2016)
Autism Spectrum Disorders (ASD) are associated with impairments in communication, social interaction, and restricted and repetitive behaviours. Therefore, communicating with children with ASD (CWASD) can be challenging even to a professional such as the speech-language therapist who provides them with speech and language therapy. This study, which analyses the interaction between a speech-language therapist and nine CWASD, aims to introduce several of the problems faced by the speech-language therapist during speech therapy sessions.The problems faced are behavioural characteristics of ASD that have to be addressed, and these problems become Smaller Short-Term Goals (SSTG) to be achieved by the speech-language therapist. Several ways in which the speech-language therapist communicates with CWASD in order to overcome the problems faced in achieving her Short-Term Goals (STG) are discussed in this study. Video-recordings of therapy sessions were analysed and interview sessions were conducted with the speech-language therapist. This study discovered that the speech-language therapistachieves her SSTG prior to achieving her STG.The findings of this study would be useful for parents of children with ASD and other speech-language therapists.